Stereotactic Ablative Radiotherapy for Oligometastatic Disease: Great Enthusiasm but Scant Evidence. Issue 5 (May 2022) - Macbeth, F.; Treasure, T.
Abstract: The prospective study Pulmonary Metastasectomy in Colorectal Cancer (N = 391) showed that expert selection was made on known prognostic features – number of metastases, tumour markers, liver involvement, interval – and patient performance and outcomes replicated follow-up studies. In the nested controlled trial all factors were well balanced and no survival difference remained.